What we know about the femininity of the future - Ю. Г. Антипкін; Т. Ф. Татарчук; О. О. Єфименко (Publishing House TRILIST, 2018)
The level of awareness about the problems of maintaining health and the quality of life in menopause is an extremely important issue not only among women of the appropriate age, but also among doctors of various specialties. Founded on the initiative of the specialists of the State Institution "E.M. Lukyanova Institute of Pediatrics, Obstetrics and Gynecology of the NAMS of Ukraine", the social and information project "Femininity of the Future" is aimed specifically at assessing the health status, awareness and frequency of the examination of women aged 40+; drawing attention to the need for regular examination and application of modern medical devices and technologies, identification of a group of high cardiovascular risk and the risk of development of oncological pathology, compiling relevant registers, increasing the level of knowledge among physicians of various specialties on modern approaches to the prevention, diagnosis and treatment of climacteric disorders. The obtained intermediate results of the program make it possible to introduce practical recommendations for raising awareness and reducing risks among women, and to optimize the training of doctors, which is what the population needs at this time. The continuation of the social and information project "Femininity of the Future" in 2018-2020 provides us with more opportunities to conduct a broad educational program to preserve the quality of life, the social activity of women in the post-productive period and methods for reducing the risks of developing cardiovascular and oncological pathologies among: doctors of related specialties, women of pre-menopausal age; women who are already in the menopause period (without manifestations of the climacteric syndrome and in its presence); to develop fundamental new technologies both in medicine and in other spheres of public life. The creation of an online version of the project in 2018 will ensure a qualitatively new level of its implementation.